The Impact of the Safe and Successful Youth Initiative (SSYI) on City-Level Youth Crime Victimization Rates - Petrosino, Anthony; Turner, Herbert; Hanson, Thomas; Fronius, Trevor; Campie, Patricia; Cooke, Cailean (Journal of MultiDisciplinary Evaluation, 2017)
Background: The physical, emotional, and financial costs resulting from youth violence are well documented. Purpose: This article summarizes the results of a quasi-experimental evaluation study to test a youth violence intervention program in eleven cities in Massachusetts. Setting: In 2011, Massachusetts initiated the Safe and Successful Youth Initiative (SSYI), which provides a comprehensive public health approach for young men believed to be at “proven risk” for being involved with firearms. Intervention: The SSYI program components include: (1) Specific identification of young men, ages 14-24, at highest risk for being involved in firearms violence; (2) Use of street outreach workers to find these young men, assess their needs, and act as brokers for services; (3) The provision of a continuum of comprehensive services including education, employment, and intensive supervision. Eleven cities with the highest count of violent offenses reported to the police in 2010 were selected for SSYI funding in 2011 and began implementing the program. Research Design: Short-interrupted time series design with a comparison group. The observed and predicted trends in monthly violent victimization rates for the 11 SSYI cities were compared to the next 23 cities (as they ranked in reported violent crime in 2010). Data Collection and Analysis: Using police incident data, researchers examined SSYI's impact on monthly city level violent crime, aggravated assault and homicide rates for persons ages 14-24. Findings: Results indicated that SSYI had a statistically significant and positive impact on reducing the number of victims of violent crimes, aggravated assaults, and homicides per month that were reported to the police. A city with SSYI has approximately 60 fewer victims of violence each year, ages 14-24, per 100,000 citizens over the post-intervention period.